Pengaruh Program Kampus Merdeka terhadap Perkembangan Diri Mahasiswa Universitas Sultan Ageng Tirtayasa - Mohamad Rizqi Mubarok; Alfiandy Warih Handoyo; Bangun Yoga Wibowo (Lembaga Pengembangan Kinerja Dosen, 2025)
This study stems from the growing need to support university students' self-growth during early adulthood, a critical phase in preparing for independence and future careers. The Merdeka Belajar–Kampus Merdeka (MBKM) initiative, introduced by Indonesia’s Ministry of Education, provides diverse learning experiences beyond the classroom that are expected to foster personal development. The objective of this research is to evaluate the impact of the MBKM program on various dimensions of student self-development, including cognitive, emotional, and social growth. Employing a quantitative research method, data were gathered through surveys distributed to students who took part in the program. The questionnaire measured specific indicators of personal development. Results indicate that the MBKM program significantly and positively contributes to the self-development of participants. Students demonstrated enhanced critical thinking, emotional intelligence, and interpersonal as well as leadership skills. These findings suggest that experiential learning opportunities such as those offered by MBKM play a vital role in nurturing students' maturity and preparing them for professional challenges. As a result, universities are encouraged to embed similar programs within their curriculum to promote comprehensive student development..